(untitled) (LACCEI, 2024)
The growing problem of waste generation generates a negative impact not only on ecosystems but also on an economic level. This research seeks to evaluate the degradative capacity of Hermetia illucens larvae to take advantage of organic waste product of anthropogenic activity in the city of Cajamarca, Peru. The culture of approximately 20,000 Hermetia illucens larvae was carried out on 10 kg of substrate composed of organic waste under adequate environmental conditions for a period of 15 days, determining that the larvae present an efficiency of 64.3% degrading organic waste, at their At the same time, an increase in mass of the larvae in the prepupal state of 4.97 Kg was evidenced, which contains a high value of proteins and usable fats. Therefore, this research presents an innovative strategy that promotes the cultivation of protein, the valuation of organic waste and suggests a promising solution to the problems of waste management.